Andi Ibrahim Masdar's Strenght Analysis at the Golkar Party of Polewali Mandar Regency - Asriani; Taufik Ikhsan; Nizar (Dinasti Research, 2025)
The presence of the Golkar party in the areas is intrinsically linked to the authority and resources wielded by its chairman. In the Mandar mayoral race, Golkar, during the New Order period, leveraged Masdar's influence derived from a bureaucratic foundation. Following Masdar's leadership in the Golkar Party, his son Andi Ibrahim Masdar assumed leadership. Internal issues within the Golkar party prompted Andi Ibrahim Masdar to resign, thus leading to his replacement by Samsul Mahmud. Despite Andi Ibrahim Masdar's departure from the Golkar Party, he retains devoted cadres. This study seeks to evaluate the current influence of Andi Ibrahim Masdar within the Golkar Party. The power of Andi Ibrahim Masdar will be examined through the lens of Pierre Bourdieu's capital theory and Suzanna Keller's elite theory. This study employs a qualitative methodology through in-depth interviews with multiple informants knowledgeable about the issue to generate a thorough analysis. The study's findings indicate that Andi Ibrahim Masdar emerged as a pivotal elite inside the Golkar Party due to his possession of social capital, cultural capital, and financial capital, hence affording him distinct advantages over other party cadres.